Biodiversity and biogeographic affiliation of Bryozoa from King George Island (Antarctica). Issue 6 (18th August 2018) - Krzeminska, Malgorzata; Sicinski, Jacek; Kuklinski, Piotr
Abstract : King George Island (KGI), which is located between the Antarctic and South American continents, may play a crucial role in the exchange of Bryozoa amongst the various Antarctic sectors and across the Polar Front. Knowledge regarding the biological diversity of this area could help us understand the evolution of the Antarctic ecosystem and its connectivity to the South American continent as well as the colonization ability of particular species. Here, we investigate the patterns of diversity and biogeographic affiliation of the cheilostome Bryozoa from KGI and the surrounding areas. Of 114 identified taxa from a depth range of 6–492 m, 26 species were reported for the first time in KGI. The most speciose genera were Camptoplites, Osthimosia, Smittina, and Cellarinella . Species richness at KGI consisted of 70% of the total bryozoans at the South Shetland Islands (SSI). Fifty-nine per cent of the bryozoans from KGI are endemic to Antarctica, which closely reflects the previously estimated endemism rate for bryozoans and other Antarctic taxa. Cluster analysis indicated that the strongest faunal links of SSI bryozoans were with Antarctic Peninsula assemblages, corresponding to the physical distance between both locations. The biogeographic similarities between SSI and South America confirm the broad trend of existing Antarctic–South American faunal links previously observed in bryozoans and many other taxa and indicate that SSI might be an important transitional zone between Antarctica and South America.